2016
DOI: 10.1038/aps.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppresses the growth of human non-small cell lung cancer via inducing estrogen sulfotransferase and inactivating estrogen

Abstract: DEX suppresses the growth of A549 xenograft tumors via inducing EST and decreasing estradiol levels in tumor tissues, suggesting that DEX may be used as anti-estrogenic agent for the treatment of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…[64][65][66][67] Proliferation is integral to the development and maintenance of the placenta, and alterations in trophoblast proliferation have been implicated in preeclampsia. A, Schematic representation of GR binding sites either overlapping or in close proximity to the chromosomal location of SERPINE1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66][67] Proliferation is integral to the development and maintenance of the placenta, and alterations in trophoblast proliferation have been implicated in preeclampsia. A, Schematic representation of GR binding sites either overlapping or in close proximity to the chromosomal location of SERPINE1.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in the proliferation rate represent another mechanism by which the rate of wound healing may be reduced following cancer cell types. [64][65][66][67] Proliferation is integral to the development and maintenance of the placenta, and alterations in trophoblast proliferation have been implicated in preeclampsia. 68 One recent study demonstrated decreased rates of proliferation of EVTs for women with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…D2DR antagonists have been used as adjuvants of chemotherapy drugs for cancer therapy [12] , and the anti-cancer effects of DEX for drug-resistant and metastatic cancer has been documented several times [6,7,[9][10][11] . Moreover, in our previous studies [6,7] , DEX exerted a better anti-cancer effect than traditional chemotherapeutics such as gemcitabine and tamoxifen, and the effect might be further improved when combined with other agents [7] . These prior studies prompted us to investigate the anti-cancer effects of DEX in combination with SUL as well as the underlying mechanisms in drug-resistant and metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX) is a synthetic glucocorticoid that is frequently used in the clinic. Several published studies have demonstrated the anti-cancer effects of DEX as a single agent [6][7][8][9][10][11] . For estrogen receptor positive (ER+) breast cancer, DEX can significantly antagonize the systemic estrogens by the glucocorticoid receptor-mediated activation of estrogen sulfotransferase, which results in inhibition of breast cancer [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (DEX) is a type of synthetic glucocorticoid that is widely used in the clinical setting. Several pre-vious studies have demonstrated the anti-cancer efficacy of DEX in xenograft breast tumor or other tumor models based on its inhibitory effect on active estrogens in the circulation and regulation of anti-inflammatory cytokines or other factors related to tumor progression [3][4][5][6][7][8][9] . In our previous studies, DEX had a greater suppression effect than general chemotherapeutic drugs, such as epirubicin and gemcitabine, in breast cancer treatment [4,10] .…”
Section: Introductionmentioning
confidence: 99%